ANALISIS PENERAPAN KESELAMATAN DAN KESEHATAN KERJA (K3) DALAM MEMINIMALISIR RESIKO KERJA PADA PT. POS INDONESIA (PERSERO) KANTOR CABANG GUNUNGSITOLI - Irvan Zebua, Ican Irvan; Baene, Eduar; Telaumbanua, Eliagus; Zebua, Emanuel (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Balikpapan, 2024)
In carrying out their duties, employees and office staff of PT. Pos Indonesia (Persero) Gunungsitoli Branch is faced with several occupational safety and health (K3) challenges. Observation data shows that as many as 75% of accidents occur in the field during package delivery, 15% occur during sorting activities, and the remaining 10% occur in administrative activities. Of the total accidents, 75% are caused by human error, such as carelessness or lack of knowledge about safety practices. Meanwhile, 25% was caused by unsafe and intensive environmental conditions, including storage facilities that were not neatly arranged and lack of warning signs. The aim of this research is to determine the Implementation of Occupational Safety and Health (K3) at PT. Pos Indonesia (Persero) Gunungsitoli Branch Office. This research method uses qualitative research with a descriptive approach. The research results show that PT. Pos Indonesia (Persero) Gunungsitoli Branch Office has so far implemented occupational safety and health implementation but it has not been optimal so there is still a lot that needs to be improved, including increasing K3 awareness and improving facilities and infrastructure. The conclusion of this research is that work accidents that occur are generally due to a lack of awareness and compliance with applicable K3 regulations, as well as a lack of work safety equipment. So it is recommended to make efforts to identify occupational safety and health practices, including analyzing compliance with regulations, as well as providing and improving facilities and infrastructure.